PEMANFATAN LAHAN PEKARANGAN UNTUK PERTANIAN ORGANIK DI BANTUL, YOGYAKARTA - Endah Wahyurini; Suranto Suranto; Suratna Suratna (Dharma: Jurnal Pengabdian Masyarakat, 2022)
During the Covid-19 pandemic, some people experienced difficulties due to declining family income. The community service team and women farmer groups in Bantul Regency saw a business opportunity by utilizing the yard around the house for organic farming. Organic farmers receive training and assistance from the service team so that they are able to grow organic vegetables for their own use and sell to consumers. The women farmers are also equipped with an understanding of farmland layouts, online marketing, and simple accounting. The results of this program are savings in family expenses and an increase in family income. This program is very helpful for women farmers in Bantul, Yogyakarta.